Risk stratification by noninvasive tests in patients with metabolic dysfunction-associated steatotic liver disease - Hye Won Lee; Jae Seung Lee; Mi Na Kim; Beom Kyung Kim; Jun Yong Park; Do Young Kim; Sang Hoon Ahn; Seung Up Kim (Clinical and Molecular Hepatology)
Background/Aims Recently, the Korean Association for the Study of the Liver (KASL) introduced a noninvasive test-based approach that uses the fibrosis-4 (FIB-4) index followed by vibration-controlled transient elastography (VCTE) to identify high-risk patients with metabolic-associated steatotic liver disease (MASLD). In this study, the KASL two-step approach was validated by assessing the risk of liver-related event (LRE) development. Methods We retrospectively analyzed 8,131 patients with MASLD who underwent VCTE between 2012 and 2020. The index date was defined as the date of the VCTE measurement. Using the KASL two-step approach (FIB-4 index and subsequent VCTE), patients were stratified into four groups (low-, intermediate-low-, intermediate-high-, and high-risk groups). Outcomes, including LREs such as decompensation (DCC) or hepatocellular carcinoma (HCC) were evaluated. Results During the follow-up (median 46.6 months), 86 (1.1%) patients developed LREs (39 [0.5%] with DCC and 47 [0.6%] with HCC). The KASL two-step approach classified 67.6%, 17.7%, 5.7% and 9.0% of patients in the low-, intermediate-low-, intermediate-high-, and high-risk groups, respectively. The cumulative incidences of LREs increased proportionally according to risk stratification (0.07%, 0.10%, 0.29%, and 1.51% at 3 years and 0.35%, 0.26%, 1.94% and 5.46% at 5 years). The overall accuracy in predicting LREs ranged from 67.7–99.8%. The FIB-4 index and subsequent Agile3+, Agile 4, or FibroScan aspartate aminotransferase scores showed similar predictive abilities compared to the KASL approach. Conclusions The KASL two-step approach is an effective and practical method for risk stratification in patients with MASLD, optimizing patient care through early identification of high-risk individuals.